Polyethylene powder and its molded body
By using polyethylene powder prepared under specific conditions, the gel viscosity control problem and molded body dimensional stability problems in wet extrusion method are solved, and the effects of few film defects, small pressure boost of the extruder and low heat shrinkage are achieved. It is suitable for applications such as battery separators.
Patent Information
- Application Number
- CN202180017214.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-05-29
- Filing Date
- 2021-05-20
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2041-05-20
AI Technical Summary
When the existing wet extrusion method increases the proportion of ultra-high molecular weight polyethylene, the gel viscosity increases, resulting in fiber wire breakage, microporous membrane film defects, or pressure boost of the extruder, and the dimensional stability of the molded body is poor.
By using polyethylene powder that meets the specific gel preparation and viscosity change rate measurement conditions, gels with a viscosity change rate of above -0.8 Pas/°C and below 0.0 Pas/°C were prepared. Combined with appropriate branched structure and polymerization conditions, the intrinsic viscosity of the polyethylene powder and the viscosity of the gel were controlled.
Polyethylene powder with few film defects, small pressure boost of the extruder, small heat shrinkage rate of the molded body and less relaxation over time is achieved, and is suitable for use in battery separators and other applications.
Smart Images

Figure CN115175960B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to polyethylene powder and a molded body thereof. Background Art
[0002] Polyethylene is easily melt-processed, and polyethylene molded products have high mechanical strength, chemical resistance, and excellent rigidity. Therefore, it has been used as a material for various applications such as films, sheets, microporous films, fibers, foams, and tubes.
[0003] In particular, ultra-high molecular weight polyethylene has higher mechanical strength, excellent lubricity and abrasion resistance, and excellent chemical stability and long-term reliability, and therefore has high practical applicability.
[0004] As a common method for molding ultra-high molecular weight polyethylene, wet extrusion can be cited. Wet extrusion refers to a method in which ultra-high molecular weight polyethylene powder is dissolved in a solvent to obtain a gel adjusted to a low viscosity, the gel is extruded, and then the solvent is removed to obtain a molded body. The wet extrusion method can be used as a molding method for fibers and microporous membranes (for example, refer to Patent Document 1).
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 2-21559 Summary of the invention
[0008] Problems to be solved by the invention
[0009] In the wet extrusion method, in order to improve the productivity of the molded body, it is necessary to appropriately control the viscosity of the gel. In the extrusion process of the wet extrusion method, smooth molding can be performed by appropriately controlling the viscosity of the substance (gel) obtained by dissolving ultra-high molecular weight polyethylene in a solvent, but the control of the viscosity of the gel at this time is mainly performed by adjusting the extrusion temperature or adjusting the proportion of ultra-high molecular weight polyethylene in the gel.
[0010] Regarding the proportion of ultra-high molecular weight polyethylene in the gel, since reducing this proportion leads to a decrease in the yield of the molded body, this proportion is preferably as high as possible. On the other hand, when the proportion of ultra-high molecular weight polyethylene in the gel is increased, the viscosity of the gel increases. Regarding the extrusion temperature, there is generally a tendency that the higher the temperature, the lower the viscosity of the gel, so from the perspective of moldability, the extrusion temperature is set as high as possible. However, when the extrusion temperature is increased, there is a tendency to produce micro-crosslinked products and burns in the extruder, and the following problems arise: broken fibers of the fibers, film defects of the microporous membrane, or a pressure increase in the extruder caused by clogging of the mesh of the extruder screen. Therefore, there is a need for an ultra-high molecular weight polyethylene that can increase the proportion of ultra-high molecular weight polyethylene in the gel and reduce the viscosity of the gel. However, there is currently a problem that an ultra-high molecular weight polyethylene that can meet this requirement cannot be obtained.
[0011] Another problem is the dimensional stability of the molded product.
[0012] In the molding of fibers and microporous films, a step of stretching the molded body is performed to impart strength. However, there is a problem that residual stress remains in the molded body, causing the molded body to shrink over time, and sufficient dimensional stability cannot be obtained for practical purposes.
[0013] Regarding such a problem of dimensional stability, regarding fibers, for example, Japanese Patent Application Publication No. 2019-90136 discloses fibers whose creep resistance is improved by using ultra-high molecular weight polyethylene having a predetermined primary structure and thermal properties.
[0014] In addition, the dimensional stability of the microporous film can be evaluated by physical properties such as heat shrinkage. Regarding the heat shrinkage, for example, Japanese Patent Application Laid-Open No. 2011-233542 discloses a microporous film in which the heat shrinkage is reduced by adjusting the metal content.
[0015] However, the techniques disclosed in these conventionally known documents have a problem that they cannot simultaneously solve the above-mentioned problems of productivity of the molded article and reduction in viscosity of the gel.
[0016] In addition, in the case of a microporous membrane, a membrane with less relaxation caused by shrinkage over time at room temperature can be said to have high dimensional stability. However, in the prior art, there has been insufficient research on raw materials to improve such dimensional stability, and there is a problem that a microporous membrane with sufficient dimensional stability cannot be obtained.
[0017] Therefore, in view of the above problems, an object of the present invention is to provide a polyethylene powder having few film defects in a molded product, small extruder pressure increase, small thermal shrinkage of the molded product, and little relaxation of the molded product over time.
[0018] Means used to solve problems
[0019] The present inventors have conducted intensive studies to solve the above problems and, as a result, have found that a polyethylene powder satisfying prescribed physical properties defined by melt viscoelasticity measurement can solve the above problems, thereby completing the present invention.
[0020] That is, the present invention is as follows. [1]
[0022] A polyethylene powder, wherein the polyethylene powder satisfies the following (requirement 1) and (requirement 2),
[0023] (Requirement 1): The viscosity change rate of the gel obtained under the following <Gel Preparation Conditions> under the following <Viscosity Change Rate Measurement Conditions> is -0.8 Pas / °C or more and 0.0 Pas / °C or less.
[0024] <Gel preparation conditions>
[0025] Using a torque rheometer (manufactured by Toyo Seiki Co., Ltd., model 4C150, mixer model R-60), 28 g of liquid paraffin having an average molecular weight greater than or equal to 450 g / mol and less than 550 g / mol, 12 g of polyethylene powder and 0.4 g of tetrakis[methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate)]methane were kneaded for 10 minutes at a set temperature of 200°C and a rotation speed of 50 rpm to obtain a gel.
[0026] <Viscosity change rate measurement conditions>
[0027] According to the flow characteristics test using a capillary die specified in JIS K7199, a capillary die with a capillary diameter of 0.77 mm, a length of 50.80 mm, and an inflow angle of 90° was used, with a piston speed of 10 mm / min (shear rate of 266 s -1 ) The viscosity (Pas) at set temperatures of 200°C and 230°C was measured, and the viscosity change rate (Pas / °C) was calculated according to the following formula (1).
[0028]
[0029] (In formula (1), η(A, B) represents the shear rate As -1 , the viscosity is measured under the conditions of temperature B℃. )
[0030] (Requirement 2): The intrinsic viscosity (IV) is 1.5 dL / g or more and less than 18.0 dL / g. [2]
[0032] The polyethylene powder as described in [1] above, wherein at a shear rate of 266 s-1 , the viscosity η(266,200) of the gel at a set temperature of 200° C. is greater than or equal to 100 Pas and less than or equal to 300 Pas. [3]
[0034] The polyethylene powder according to the above [1] or [2], wherein the gel obtained by the <Gel Preparation Conditions> has a viscosity of 0.1% at a shear rate of 11 s according to the <Viscosity Change Rate Measurement Conditions>. -1 , the viscosity of the gel measured at a set temperature of 200°C and at a shear rate of 533s -1 , log(η(11,200) / η(533,200)) of the viscosity of the gel measured at a set temperature of 200° C. is 1.00 or more and 1.80 or less. [4]
[0036] The polyethylene powder according to any one of [1] to [3] above, wherein the polyethylene powder is an ethylene homopolymer. [5]
[0038] The polyethylene powder according to any one of the above [1] to [4], wherein the isothermal crystallization time of the polyethylene powder at 125° C. obtained under the following “Isothermal Crystallization Time Measurement Conditions” is less than 7.0 minutes.
[0039] <Isothermal crystallization time measurement conditions>
[0040] Step A1: Maintain at 50°C for 1 minute, then increase the temperature to 180°C at a rate of 10°C / min.
[0041] Step A2: Maintain at 180°C for 5 minutes, then cool to 125°C at a cooling rate of 80°C / min.
[0042] Step A3: Maintain at 125° C. The time when the temperature reaches 125° C. is defined as the starting point (0 minutes), and the time when the exothermic peak due to crystallization is obtained is defined as the isothermal crystallization time. [6]
[0044] A molded product, wherein the molded product is a molded product of the polyethylene powder according to any one of [1] to [5] above. [7]
[0046] The molded article according to the above-mentioned [6], wherein the molded article is a battery separator. [8]
[0048] The molded article according to the above-mentioned [6], wherein the molded article is a separator for a lithium ion secondary battery.
[0049] Effects of the Invention
[0050] According to the present invention, it is possible to provide a polyethylene powder having a molded product with few film defects, a small extruder pressure increase, a small thermal shrinkage of the molded product, and little relaxation of the molded product over time. DETAILED DESCRIPTION
[0051] Hereinafter, a mode for carrying out the present invention (hereinafter also referred to as “the present embodiment”) will be described in detail.
[0052] It should be noted that the following embodiments are examples for explaining the present invention, and are not intended to limit the present invention to the following contents. The present invention can be implemented with various modifications within the scope of the gist of the invention.
[0053] [Polyethylene powder]
[0054] The polyethylene powder of the present embodiment satisfies the following (requirement 1) and (requirement 2).
[0055] (Requirement 1): The viscosity change rate of the gel obtained under the following <Gel Preparation Conditions> under the following <Viscosity Change Rate Measurement Conditions> is -0.8 Pas / °C or more and 0.0 Pas / °C or less.
[0056] <Gel preparation conditions>
[0057] Using a torque rheometer (manufactured by Toyo Seiki Co., Ltd., model 4C150, mixer model R-60), 28 g of liquid paraffin having an average molecular weight greater than or equal to 450 g / mol and less than 550 g / mol, 12 g of polyethylene powder and 0.4 g of tetrakis[methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate)]methane were kneaded for 10 minutes at a set temperature of 200° C. and a rotation speed of 50 rpm to obtain a gel.
[0058] <Viscosity change rate measurement conditions>
[0059] According to the flow characteristics test using a capillary die specified in JIS K7199, a capillary die with a capillary diameter of 0.77 mm, a length of 50.80 mm, and an inflow angle of 90° was used, with a piston speed of 10 mm / min (shear rate of 266 s -1 ) The viscosity (Pas) at set temperatures of 200°C and 230°C was measured, and the viscosity change rate (Pas / °C) was calculated according to the following formula (1).
[0060]
[0061] In formula (1), η(A,B) represents the shear rate As -1 The viscosity (Pas) of the gel measured under the conditions of B℃ and temperature.
[0062] That is, η(266,230) means that at a shear rate of 266s -1 The viscosity of the gel measured at a temperature of 230°C (Pas), η(266,200) means the viscosity of the gel at a shear rate of 266s -1 , viscosity of the gel measured at 200°C (Pas).
[0063] (Requirement 2): The intrinsic viscosity (IV) is 1.5 dL / g or more and less than 18.0 dL / g.
[0064] The polyethylene powder of the present embodiment can obtain the following effects (i) to (iv) by having the above-mentioned configuration.
[0065] (i) The polyethylene powder of this embodiment has a small pressure increase in the extruder during the extrusion molding process.
[0066] (ii) A molded product formed using the polyethylene powder of this embodiment, such as a micro-crosslinked product of a microporous membrane, has few defects such as burns, stains, and pinholes, and is suitable as a battery separator.
[0067] (iii) A molded product, such as a microporous film, molded using the polyethylene powder of this embodiment has little sag and is excellent in appearance, and is suitable as a battery separator.
[0068] (iv) A molded product, such as a microporous film, molded using the polyethylene powder of this embodiment has a small thermal shrinkage rate and is suitable as a battery separator.
[0069] Hereinafter, the structure of the polyethylene powder according to the present embodiment will be described.
[0070] (Polyethylene)
[0071] The polyethylene powder of the present embodiment is composed of an ethylene polymer.
[0072] The ethylene polymer preferably has 99.5 mol% or more of its structural units consisting of ethylene units, more preferably has 99.8 mol% or more of its structural units consisting of ethylene units, and further preferably has 100 mol% of its structural units consisting of ethylene units, that is, is an ethylene homopolymer.
[0073] Since the polyethylene powder of the present embodiment is an ethylene homopolymer, the strength of the molded product tends to be improved.
[0074] In order to increase the polymerization rate or improve processability during film formation, the ethylene polymer constituting the polyethylene powder of the present embodiment may be a copolymer into which branches are introduced by adding a very small amount of a copolymerization component such as α-olefin.
[0075] When the ethylene polymer is a copolymer, the copolymerization component is not limited to the following, and examples thereof include α-olefins and vinyl compounds.
[0076] The α-olefins are not limited to the following, and examples thereof include α-olefins having 3 to 20 carbon atoms, and specifically include propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, and the like.
[0077] Examples of the vinyl compound include, but are not limited to, vinylcyclohexane, styrene, and derivatives thereof.
[0078] Furthermore, non-conjugated polyenes such as 1,5-hexadiene and 1,7-octadiene may be used as other comonomers as necessary.
[0079] The copolymerization components may be used alone or in combination of two or more.
[0080] When the ethylene polymer constituting the polyethylene powder of the present embodiment is a copolymer, the amount of other comonomers in the copolymer can be confirmed by NMR method or the like.
[0081] (Polyethylene powder)
[0082] The polyethylene powder of this embodiment is in powder form, and its average particle size is not particularly limited, but is preferably 500 μm or less, more preferably 300 μm or less, and further preferably 150 μm or less. In addition, the average particle size of the polyethylene powder is preferably 5 μm or more, and more preferably 10 μm or more.
[0083] The average particle size of the polyethylene powder of this embodiment is 500 μm or less, so that the solubility of the polyethylene powder in the solvent can be further improved, and the undissolved residue that damages the performance and appearance of the molded body can be reduced. In addition, the average particle size of the polyethylene powder is 5 μm or more, so that the scattering of the powder can be suppressed, so the handleability is further improved, and when added to the solvent, the agglomeration can be suppressed, so there is a tendency to more easily form a uniform slurry.
[0084] It should be noted that the average particle size mentioned here refers to the particle size when the cumulative mass reaches 50%, that is, the median particle size.
[0085] (Density of polyethylene powder)
[0086] The density of the polyethylene powder of this embodiment is not particularly limited, but is preferably 910 kg / m 3 Above and 980kg / m 3 Below, more preferably 915kg / m3 Above and 970kg / m 3 Below, more preferably 920kg / m 3 Above and 965kg / m 3 the following.
[0087] It should be noted that the density of the above polyethylene powder is the true density of the polymer.
[0088] The density of polyethylene powder is 910kg / m 3 Above and 980kg / m 3 Next, a molded body including the polyethylene powder of the present embodiment tends to have excellent strength.
[0089] (Viscosity change rate)
[0090] The viscosity change rate of the gel obtained by the above-mentioned <Gel Preparation Conditions> of the polyethylene powder of this embodiment under the above-mentioned <Viscosity Change Rate Measurement Conditions> is greater than or equal to -0.8 Pas / °C and less than or equal to 0.0 Pas / °C, preferably greater than or equal to -0.5 Pas / °C and less than or equal to 0.0 Pas / °C, and more preferably greater than or equal to -0.2 Pas / °C and less than or equal to 0.0 Pas / °C.
[0091] The polyethylene powder of this embodiment has a higher molecular weight than general-purpose polyethylene used in film molding, blow molding, etc., and therefore has molecular entanglement not only in the state of single polyethylene but also in the state of gel obtained by the above-mentioned <Gel Preparation Conditions>. It is known that polyethylene having such molecular entanglement has extremely low temperature dependence of viscosity in a specific temperature (or shear rate) region (rubber-like flat region). The viscosity change rate under the above-mentioned <Viscosity Change Rate Measurement Conditions> is the result obtained by measuring the temperature dependence of viscosity in the rubber-like flat region, and the viscosity change rate thus obtained represents the degree of molecular entanglement.
[0092] In the polyethylene powder of this embodiment, the gel obtained by the above <Gel Preparation Conditions> is characterized in that the viscosity change rate is within a specific range. This is because the polyethylene powder of this embodiment has molecular entanglement within a specific range, that is, has molecular entanglement within an appropriate range.
[0093] When the viscosity change rate of the gel obtained by using the polyethylene powder of the present embodiment and in accordance with the above-mentioned <Gel Preparation Conditions> is -0.8 Pas / °C or more and 0.0 Pas / °C or less, the following effects can be obtained.
[0094] That is, when a battery separator is manufactured using polyethylene by wet extrusion, the viscosity of the gel is adjusted to ensure good processability (film forming properties) and to obtain high productivity (yield), the polyethylene content in the gel is increased in most cases, and the temperature is set high to perform the extrusion process. However, when the extrusion process is performed under high temperature conditions, there is a tendency for defects caused by micro-crosslinking and burning to occur in the molded body, or the pressure increase of the extruder becomes too large.
[0095] On the other hand, the gel using the polyethylene powder of this embodiment has a low viscosity change rate and can maintain a high polyethylene ratio even at a relatively low temperature, thereby ensuring high productivity (yield) while reducing the occurrence of defects in the molded body and the pressure increase of the extruder.
[0096] In addition, as described above, the gel using the polyethylene powder of the present embodiment has a specific range of molecular entanglement. In the manufacture of battery separators, there are two characteristic processes of film stretching and thermal fixation. In these processes, the polyethylene molecules are oriented after stretching and orientation, and the orientation is relaxed. By properly controlling the orientation and relaxation, the balance of physical properties such as the strength and thermal shrinkage of the film can be adjusted. The degree of molecular entanglement has a great influence on the orientation and relaxation. Since the degree of entanglement of the gel using the polyethylene powder of the present embodiment is within an appropriate range, it is possible to reduce thermal shrinkage and suppress the occurrence of relaxation over time.
[0097] The viscosity change rate calculated by the above formula (1) of the gel using the polyethylene powder of the present embodiment can be controlled by giving the polyethylene an appropriate branched structure. That is, when the polyethylene primary structure such as the length of the side chain and the spacing of the side chains is controlled to give the polyethylene an appropriate branched structure, molecular constraints are generated by the branching and entanglement of the polyethylene molecules, and thus the viscosity change rate tends to be reduced.
[0098] As a method for imparting an appropriate branched structure to polyethylene, there can be cited a method of polymerizing in an environment where macromonomers are easily generated and coordination is easily generated. Specifically, there can be cited methods of polymerizing using a catalyst with a saturated active site density; making the polymerization temperature above 80°C; making the slurry concentration above 35% by mass; making the catalyst activity below 30,000 g-PE / g-catalyst (30,000 g of polyethylene per 1 g of catalyst); and continuously supplying the catalyst at a temperature 50°C or more lower than the polymerization temperature.
[0099] The viscosity change rate of the gel using the polyethylene powder of the present embodiment can be measured by the method described in the Examples described later.
[0100] (Intrinsic viscosity (IV) of polyethylene powder)
[0101] The intrinsic viscosity (IV) of the polyethylene powder of this embodiment is greater than or equal to 1.5 (dL / g) and less than 18.0 (dL / g), preferably greater than or equal to 2.0 (dL / g) and less than 15.0 (dL / g), and more preferably greater than or equal to 2.4 (dL / g) and less than 7.1 (dL / g). By making the intrinsic viscosity (IV) of the polyethylene powder within the above range, the mechanical strength and processability of the molded body can be taken into account with excellent balance.
[0102] The intrinsic viscosity (IV) can be measured by the method described in the examples described below.
[0103] The intrinsic viscosity (IV) of the polyethylene powder of this embodiment can be controlled within the above numerical range by using a catalyst described later and appropriately adjusting polymerization conditions, etc. Specific polymerization conditions include allowing hydrogen to exist in the polymerization system and / or changing the polymerization temperature, thereby enabling the intrinsic viscosity (IV) to be controlled.
[0104] (Gel viscosity η(266,200))
[0105] The polyethylene powder of the present embodiment is used to obtain a gel according to the <Gel Preparation Conditions> described above, and the gel is measured at a shear rate of 266 s according to the <Viscosity Change Rate Measurement Conditions> described above. -1 The viscosity η(266,200) of the gel measured at a set temperature of 200°C is preferably 100 Pas to 300 Pas, more preferably 120 Pas to 250 Pas, and further preferably 140 Pas to 230 Pas.
[0106] When the viscosity η (266, 200) is within the above range, the moldability of the wet extruded microporous membrane is good, which is preferred.
[0107] The viscosity η (266,200) of the above gel can be controlled by adjusting the molecular weight, copolymer amount, branched structure of polyethylene, adding a lubricant as an additive to polyethylene, etc.
[0108] The molecular weight of polyethylene depends on the amount of copolymer, branched structure, and lubricant, and as the molecular weight increases, the viscosity η(266,200) of the gel tends to increase. In addition, as the amount of copolymer increases, the viscosity η(266,200) of the gel tends to decrease.
[0109] The amount of lubricant also depends on the type of lubricant, but generally increasing the amount added to about 2000 ppm tends to reduce the viscosity η(266,200) of the gel. Even if the amount added is further increased, the reduction in the viscosity η(266,200) of the gel decreases.
[0110] The viscosity η (266,200) of the gel can be measured by the method described in the Examples described later.
[0111] (log(η(11,200) / η(533,200)))
[0112] The polyethylene powder of the present embodiment is used to obtain a gel according to the <Gel Preparation Conditions> described above, and the gel is measured at a shear rate of 11 s according to the <Viscosity Change Rate Measurement Conditions> described above. -1 , the viscosity of the gel measured at a set temperature of 200°C and at a shear rate of 533s -1 The viscosity of the gel measured at a set temperature of 200° C., log(η(11,200) / η(533,200)) is preferably 1.00 to 1.80, more preferably 1.10 to 1.60, and even more preferably 1.20 to 1.50.
[0113] log(η(11,200) / η(533,200)) represents the shear rate dependency of the viscosity of the gel.
[0114] In the process of manufacturing a battery separator using a gel prepared from polyethylene powder, the gel is deformed at a relatively high strain rate during the processes of melt kneading, sheet forming, stretching, etc. in an extruder. In the above-mentioned processes, polyethylene powders with low viscosity generally within the range that can be formed are preferred because of their high productivity. On the other hand, in the processes of cooling and transporting the sheet, it is preferred that the sheet does not deform, so polyethylene powders with high viscosity within the range that can be formed are generally preferred at this time.
[0115] In view of the above situation, by regulating the above log(η(11,200) / η(533,200)) within the above numerical range, when the polyethylene powder of this embodiment is used to manufacture a battery separator, the processability and productivity are good both in the process with a high strain rate and in the process with a low strain rate, which is preferred.
[0116] The above-mentioned log(η(11,200) / η(533,200)) is affected by the weight average molecular weight, number average molecular weight, molecular weight distribution, and entanglement amount of the polyethylene constituting the polyethylene powder of the present embodiment.
[0117] As the weight average molecular weight and the number average molecular weight increase, η(11,200) significantly increases, and thus log(η(11,200) / η(533,200)) tends to increase.
[0118] In addition, regarding the molecular weight distribution, when the distribution becomes broad, η(11,200) tends to become smaller due to the effect of the low molecular weight component, and thus log(η(11,200) / η(533,200)) also tends to become smaller.
[0119] In addition, as the amount of molecular entanglement increases, η(11,200) tends to increase, and thus log(η(11,200) / η(533,200)) also tends to increase.
[0120] That is, specific methods for controlling log(η(11,200) / η(533,200)) include, for example, controlling the molecular weight by controlling the polymerization conditions (temperature, pressure, hydrogen concentration, etc.); controlling the molecular weight distribution by controlling the catalyst preparation conditions (catalyst type, preparation temperature, preparation time); controlling the amount of entanglement by controlling the molecular branching, etc.
[0121] The above log(η(11,200) / η(533,200)) can be measured by the method described in Examples to be described later.
[0122] (Isothermal crystallization time at 125°C (minutes))
[0123] In the polyethylene powder of the present embodiment, the isothermal crystallization time obtained by the following <Isothermal Crystallization Time Measurement> is the time to obtain the exothermic peak top due to crystallization at 125° C., and is preferably less than 7.0 minutes.
[0124] <Isothermal crystallization time measurement>
[0125] Step A1: Maintain at 50°C for 1 minute, then increase the temperature to 180°C at a rate of 10°C / min.
[0126] Step A2: Maintain at 180°C for 5 minutes, then cool to 125°C at a cooling rate of 80°C / min.
[0127] Step A3: Maintain at 125° C. The time when the temperature reaches 125° C. is defined as the starting point (0 minutes), and the time when the exothermic peak due to crystallization is obtained is defined as the isothermal crystallization time.
[0128] The isothermal crystallization time of the polyethylene powder of this embodiment at 125° C. is preferably less than 7.0 minutes, more preferably less than 4.0 minutes, and further preferably less than 3.0 minutes. By making the isothermal crystallization time at 125° C. less than 7.0 minutes, the crystal size of the billet (a sheet in a state formed by an extruder) during film processing becomes smaller, and a denser pore structure can be obtained. In addition, there is no particular limitation on the lower limit of the isothermal crystallization time at 125° C., but it is preferably 1.0 minutes or more.
[0129] As a method for controlling the isothermal crystallization time, there can be cited reduction of the crystal size of polyethylene, etc. As a method for reducing the crystal size of polyethylene, it is not limited to the following methods, for example, there can be cited a method of preparing a polymerization catalyst for polyethylene under low temperature and long time conditions, etc.
[0130] The isothermal crystallization time can be specifically measured by the method described in the following Examples.
[0131] [Method for producing polyethylene powder]
[0132] The polymerization method in the method for producing polyethylene powder according to the present embodiment is not limited to the following methods, and examples thereof include methods of polymerizing ethylene or a monomer (copolymer) containing ethylene by slurry polymerization, gas phase polymerization, solution polymerization, and the like.
[0133] Among them, the slurry polymerization method is preferred because it can effectively remove the heat of polymerization.
[0134] In the slurry polymerization method, an inert hydrocarbon medium may be used as the medium, or the olefin itself may be used as the medium.
[0135] The above-mentioned inert hydrocarbon medium is not limited to the following substances, and examples thereof include: aliphatic hydrocarbons such as propane, butane, isobutane, pentane, isopentane, hexane, heptane, octane, decane, dodecane, kerosene, etc.; alicyclic hydrocarbons such as cyclopentane, cyclohexane, methylcyclopentane, etc.; aromatic hydrocarbons such as benzene, toluene, xylene, etc.; halogenated hydrocarbons such as ethyl chloride, chlorobenzene, dichloromethane, etc.; and mixtures thereof, etc.
[0136] The polymerization temperature in the method for producing the polyethylene powder of the present embodiment is preferably 80° C. or higher and 100° C. or lower.
[0137] Generally, when the polymerization temperature is 40°C or higher, industrially efficient production tends to be possible, and when the polymerization temperature is 80°C or higher, coordination of macromonomers tends to be easily induced. On the other hand, when the polymerization temperature is 100°C or lower, continuous and stable operation tends to be possible.
[0138] The polymerization pressure in the method for producing the polyethylene powder of the present embodiment is preferably 0.10 MPa to 2.0 MPa, more preferably 0.10 MPa to 1.5 MPa, and even more preferably 0.10 MPa to 1.0 MPa.
[0139] The slurry concentration (solid content ratio in the liquid phase) in the polymerization reactor in the method for producing polyethylene powder of the present embodiment is preferably 35 mass % or more and 45 mass % or less. By making the slurry concentration 35 mass % or more, there is a tendency to easily cause coordination of macromolecular monomers. On the other hand, by making the slurry concentration 45 mass % or less, there is a tendency to be able to operate continuously and stably.
[0140] In addition, the activity of the catalyst during polymerization in the method for producing polyethylene powder of the present embodiment is preferably 8,000 g-PE / g-catalyst (8,000 g of polyethylene per 1 g of catalyst) or more and 30,000 g-PE / g-catalyst (30,000 g of polyethylene per 1 g of catalyst) or less. By making the catalyst activity 8,000 g-PE / g-catalyst or more, the catalyst residue remaining in the polyethylene powder becomes a sufficiently low concentration, which is preferred. In addition, by making the catalyst activity 30,000 g-PE / g-catalyst or less, there is a tendency to easily cause coordination of macromonomers, which is preferred.
[0141] The polymerization reaction may be carried out by any of a batch method, a semi-continuous method and a continuous method, and it is particularly preferred to carry out the polymerization by a continuous method.
[0142] By continuously supplying ethylene gas, solvent (e.g., hexane), catalyst, etc. into the polymerization system, and continuously discharging ethylene gas, solvent (e.g., hexane), catalyst, etc. together with the generated polyethylene powder, it is possible to suppress the local high temperature state caused by the rapid ethylene reaction, and there is a tendency to make the polymerization system more stable.
[0143] As the catalyst component used for producing the polyethylene powder according to the present embodiment, for example, a Ziegler-Natta catalyst, a metallocene catalyst, a Phillips catalyst, etc. can be appropriately mentioned.
[0144] As the Ziegler-Natta catalyst, for example, the catalyst described in Japanese Patent No. 5767202 can be suitably used. As the metallocene catalyst, it is not limited to the following catalysts, and for example, the catalyst described in Japanese Patent Application Laid-Open No. 2006-273977 and Japanese Patent No. 4868853 can be suitably used.
[0145] The catalyst component used for producing the polyethylene powder of the present embodiment may contain a co-catalyst such as triisobutylaluminum or Tebbe's reagent.
[0146] In addition, as a catalyst used for producing the polyethylene powder of the present embodiment, it is preferable to increase the active site density as much as possible. A high active site density tends to facilitate the generation of macromonomers.
[0147] In addition, as a method of using the catalyst used in the production of the polyethylene powder of the present embodiment, it is preferred to implement the following method: a method of cooling the catalyst in a manner such that the temperature difference from the polymerization temperature is 50°C or more and 70°C or less and continuously introducing the catalyst into the polymerizer in the cooled state. By cooling the catalyst in a manner such that the temperature difference from the polymerization temperature is 50°C or more and continuously introducing the catalyst into the polymerizer in the cooled state, there is a tendency to easily cause coordination of the macromonomer. In addition, by making the temperature difference from the polymerization temperature 70°C or less, the polymerization reaction can be stably and continuously carried out.
[0148] The average particle size of the catalyst used in the method for producing polyethylene powder of the present embodiment is preferably 0.1 μm to 20 μm, more preferably 0.2 μm to 16 μm, and even more preferably 0.5 μm to 12 μm.
[0149] When the average particle size of the catalyst is 0.1 μm or more, there is a tendency to prevent the polyethylene powder obtained from scattering or adhering to a polymerization reactor, a dryer, or a product hopper.
[0150] When the average particle size of the catalyst is 10 μm or less, the polyethylene powder tends to be prevented from becoming too large and settling in the polymerization system, and problems such as clogging of the pipeline in the post-treatment step of the polyethylene powder tend to be prevented.
[0151] The particle size distribution of the catalyst is preferably as narrow as possible, and fine powder particles and coarse powder particles can be removed by sieving, centrifugal separation, or cyclone.
[0152] The method for deactivating the catalyst used in the production of the polyethylene powder is not particularly limited, but is preferably carried out after the polyethylene powder is separated from the solvent.
[0153] By adding a chemical agent for deactivating the catalyst after separation from the solvent, precipitation of the catalyst component and the like dissolved in the solvent can be suppressed, and Ti, Al, Cl and the like derived from the catalyst component can be reduced.
[0154] The chemical agent for deactivating the catalyst system is not limited to the following substances, and examples thereof include oxygen, water, alcohols, glycols, phenols, carbon monoxide, carbon dioxide, ethers, carbonyl compounds, alkynes, and the like.
[0155] The weight average molecular weight and number average molecular weight of the polyethylene powder of the present embodiment can be controlled by allowing hydrogen to exist in the polymerization system or by changing the polymerization temperature, as described in, for example, German Patent Application Publication No. 3127133.
[0156] By adding hydrogen as a chain transfer agent to the polymerization system, the weight average molecular weight and number average molecular weight of the polyethylene powder can be easily controlled within appropriate ranges.
[0157] When hydrogen is added to the polymerization system, the molar fraction of hydrogen is preferably 0 mol % to 30 mol %, more preferably 0 mol % to 25 mol %, and even more preferably 0 mol % to 20 mol %.
[0158] Examples of the solvent separation method in the method for producing the polyethylene powder of the present embodiment include decantation, centrifugal separation, and filter filtration. Centrifugal separation is preferred from the viewpoint of high separation efficiency between the polyethylene powder and the solvent.
[0159] In the method for producing the polyethylene powder of the present embodiment, it is preferred that a drying step is performed after the polyethylene powder and the solvent are separated.
[0160] The drying temperature in the drying step is preferably 50° C. or higher and 150° C. or lower, more preferably 50° C. or higher and 140° C. or lower, and further preferably 50° C. or higher and 130° C. or lower. If the drying temperature is 50° C. or higher, efficient drying can be performed. On the other hand, if the drying temperature is 150° C. or lower, drying can be performed while suppressing aggregation and thermal degradation of the polyethylene powder.
[0161] (additive)
[0162] The polyethylene powder of the present embodiment may contain, in addition to the above-mentioned components, other known components useful for the production of polyethylene powder. The polyethylene powder of the present embodiment may further contain additives such as a neutralizer, an antioxidant, and a light stabilizer.
[0163] The neutralizing agent can be used as a scavenger for chlorine contained in polyethylene or as a molding aid, etc. The neutralizing agent is not limited to the following substances, and examples thereof include stearates of alkaline earth metals such as calcium, magnesium, and barium.
[0164] The content of the neutralizing agent is not particularly limited, but is preferably 5,000 ppm or less, more preferably 4,000 ppm or less, and even more preferably 3,000 ppm or less, based on the total amount of polyethylene.
[0165] When the polyethylene powder of the present embodiment is an ethylene polymer obtained by a slurry polymerization method using a metallocene catalyst, the halogen component can be removed from the catalyst constituent components. In such a case, the neutralizing agent does not need to be used.
[0166] The antioxidant is not limited to the following, and examples thereof include phenolic antioxidants such as butylated hydroxytoluene, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate.
[0167] The content of the antioxidant is not particularly limited, but is preferably 5,000 ppm or less, more preferably 4,000 ppm or less, and further preferably 3,000 ppm or less.
[0168] The light stabilizer is not limited to the following substances, and examples thereof include benzotriazole-based light stabilizers such as 2-(5-methyl-2-hydroxyphenyl)benzotriazole and 2-(3-tert-butyl-5-methyl-2-hydroxyphenyl)-5-chlorobenzotriazole; hindered amine-based light stabilizers such as bis(2,2,6,6-tetramethyl-4-piperidinyl)sebacate and poly[{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl}{(2,2,6,6-tetramethyl-4-piperidinyl)imino)hexamethylene}{(2,2,6,6-tetramethyl-4-piperidinyl)imino}]; and the like.
[0169] The content of the light-resistant stabilizer is not particularly limited, but is preferably 5,000 ppm or less, more preferably 4,000 ppm or less, and further preferably 3,000 ppm or less.
[0170] The content of the additive contained in the polyethylene powder of the present embodiment can be determined by extracting the additive in the polyethylene powder by Soxhlet extraction using tetrahydrofuran (THF) for 6 hours, and separating and quantifying the extract by liquid chromatography.
[0171] [Molding body]
[0172] The molded product of the present embodiment is a molded product of the polyethylene powder of the present embodiment described above.
[0173] The polyethylene powder of the present embodiment is characterized in that the temperature dependence of the melt viscosity in the gel state is small, and from this point of view, it is particularly suitable for molding by wet extrusion.
[0174] The polyethylene powder gel of the present embodiment can be extruded at a high polymer concentration, i.e., a high proportion of polyethylene in the gel, even at low temperature during wet extrusion, thereby reducing defects caused by micro-crosslinking and burning, or pressure increase of the extruder. Examples of molded bodies molded by wet extrusion include microporous membranes and fibers.
[0175] (use)
[0176] The polyethylene powder molded product of this embodiment has excellent dimensional stability during heat setting and little heat shrinkage after heat setting, and is therefore suitable for battery separators, specifically secondary battery separators, especially lithium ion secondary battery separators and lead acid battery separators.
[0177] In addition, by using solid-state forming such as extrusion molding, press molding, and cutting, it can be used for linings of gears, rollers, curtain rails, pinball rails, grain storage bins, etc.; slip coatings for rubber products, ski materials and ski boots, lining materials for heavy machinery such as trucks or forklifts.
[0178] Furthermore, the polyethylene powder of the present embodiment can be used for a molded body obtained by sintering the polyethylene powder, a filter, a dust collecting material, and the like.
[0179] Example
[0180] Hereinafter, the present embodiment will be described in more detail using specific examples and comparative examples, but the present embodiment is not limited to the following examples and comparative examples.
[0181] The measurement methods of various characteristics and properties are shown below.
[0182] [Methods for measuring various characteristics and properties]
[0183] (1) Intrinsic viscosity (IV)
[0184] The intrinsic viscosity (IV) of each polyethylene powder obtained in the examples and comparative examples described below was measured in accordance with ISO 1628-3 (2010).
[0185] First, a measurement solution is prepared.
[0186] The measurement solution was prepared as follows: polyethylene powder was weighed in the range of 4.0 mg to 4.5 mg, and 20 mL of decalin (decalin obtained by adding 1 g / L of 2,6-di-tert-butyl-4-methylphenol, hereinafter referred to as decalin) that had been degassed with a vacuum pump and replaced with nitrogen was used as a solvent. The solution was dissolved by stirring at 150° C. for 90 minutes in a dissolving tube in which the air inside had been degassed with a vacuum pump and replaced with nitrogen.
[0187] As a viscosity tube, a Cannon-Fenske viscometer (manufactured by Shibata Scientific Instruments Co., Ltd.: product number-100) was used.
[0188] (2) Gel melt viscosity (η) and viscosity change rate (Pas / ℃)
[0189] The melt viscosity (η) of the gel of each polyethylene powder obtained in the examples and comparative examples described below was measured according to the following procedure in accordance with the flow characteristics test using a capillary die specified in JIS K7199.
[0190] First, 12 g of polyethylene powder, 28 g of liquid paraffin (Matsumura Oil Co., Ltd., P-350) and 0.4 g of tetrakis[methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate)]methane were fully mixed. Then, a torque rheometer (Toyo Seiki Co., Ltd., Model 4C150, Mixer Model R-60) was used to knead the mixture for 10 minutes at a set temperature of 200° C. and a rotation speed of 50 rpm to prepare a gel.
[0191] The gel was compression molded using a mold having a thickness of 1 mm according to ASTM D 1928 Procedure C to prepare a gel sheet. The prepared gel sheet was cut into strips having a length of about 5 cm and a width of about 5 mm. A capillary die having a capillary diameter of 0.77 mm, a length of 50.80 mm, and an inflow angle of 90° was set on a capillary rheometer (manufactured by Toyo Seiki Co., Ltd., Model 1D), and the cut gel sheet was put in, and the viscosity was measured.
[0192] At this time, the shear speed is set to As -1 The viscosity when measured at a temperature of B°C is referred to as η(A, B).
[0193] The viscosity change rate (Pas / °C) was calculated according to the following formula (1).
[0194]
[0195] (3) Isothermal crystallization time (minutes)
[0196] The isothermal crystallization time at 125° C. obtained under the following “Isothermal Crystallization Time Measurement Conditions” was measured using a differential scanning calorimeter (DSC).
[0197] As described below, the time when the temperature reaches 125° C. in step A3 is defined as the starting point (0 minute), and the time when the exothermic peak top due to crystallization is obtained is measured and defined as the isothermal crystallization time.
[0198] <Isothermal crystallization time measurement conditions>
[0199] Step A1: Maintain at 50°C for 1 minute, then increase the temperature to 180°C at a rate of 10°C / min.
[0200] Step A2: Maintain at 180°C for 30 minutes, then cool to 125°C at a cooling rate of 80°C / min.
[0201] Step A3: Maintain at 125°C.
[0202] (4) Preparation of microporous membrane
[0203] The twin-screw extruder should be thoroughly cleaned in advance.
[0204] The polyethylene powder and liquid paraffin were uniformly melt-kneaded by a twin-screw extruder to obtain a polyethylene melt-kneaded product (gel).
[0205] The ratio of the polyethylene powder in the gel was adjusted as follows.
[0206] When the intrinsic viscosity (IV) of the polyethylene powder is less than 3.9 dL / g, the proportion of the polyethylene powder in the gel is set to 40% by mass.
[0207] When the intrinsic viscosity (IV) of the polyethylene powder is 3.9 dL / g or more and less than 6.1 dL / g, the proportion of the polyethylene powder in the gel is set to 30% by mass.
[0208] When the intrinsic viscosity (IV) of the polyethylene powder is 6.1 dL / g or more and less than 7.1 dL / g, the proportion of the polyethylene powder in the gel is set to 27% by mass.
[0209] When the intrinsic viscosity (IV) of the polyethylene powder is 7.1 dL / g or more, the proportion of the polyethylene powder in the gel is set to 24% by mass.
[0210] The extrusion temperature was in the range of 170℃~220℃, and the shear rate was set at 266s -1 The viscosity under the condition of temperature T (°C) was set to the temperature T (°C) at which η (266, T) = 200 Pas was closest, and extrusion was carried out under the conditions of a screw speed of 170 rpm and a discharge rate of 15 kg / hour. A 100-mesh sieve was used.
[0211] Next, the molten kneaded product was extruded into a sheet using a T-die (width 250 mm) maintained at 220° C. The molten kneaded product was pressed and cooled using a metal roll whose surface temperature was controlled to 60° C., thereby obtaining a gel sheet with excellent thickness stability of 1000 μm. In order to evaluate the pressure increase of the extruder described below, extrusion was continuously performed for 8 hours.
[0212] Next, the film was stretched to 7×7 times at a stretching temperature of 125° C. using a synchronous twin-screw stretching machine, and then introduced into a methyl ethyl ketone tank, fully immersed in methyl ethyl ketone to extract and remove liquid paraffin, and then dried to remove methyl ethyl ketone.
[0213] Next, the film was stretched 1.5 times in the transverse direction at 120°C using a tenter stretching machine, and heat-set at 125°C.
[0214] Furthermore, the microporous membrane was wound around the paper tube using a winder.
[0215] (5) Film defect evaluation
[0216] The number of defects having a diameter of 0.2 mm or more present in an area of 25 cm×25 cm of the obtained microporous membrane was visually measured. The evaluation criteria are as follows.
[0217] Greater than or equal to 0 / 625cm 2 And less than 4 / 625cm 2 :○
[0218] More than or equal to 4 / 625cm 2 And less than 7 / 625cm 2 :△
[0219] 7pcs / 625cm 2 Above: ×
[0220] (6) Extruder pressure increase evaluation
[0221] In the preparation of the microporous membrane of (4) above, the pressure is measured using a resin pressure gauge installed upstream of the circuit breaker board. The difference between the average value of the resin pressure 10 minutes after the start of extrusion and the average value of the resin pressure 10 minutes before the end of extrusion is evaluated as the pressure increase. The evaluation criteria are as follows.
[0222] Greater than or equal to 0MPa and less than 0.5MPa: ○
[0223] Greater than or equal to 0.5MPa and less than 1.0MPa: △
[0224] 1.0MPa or above: ×
[0225] (7) Relaxation evaluation
[0226] The microporous membrane prepared in (4) was pulled out for about 3 m, held at four corners and horizontally stretched in the air, and local slack that could be confirmed by visual observation was evaluated. The local slack was evaluated to what extent it deteriorated after being left at room temperature for one week while being held on a roll compared to that immediately after the membrane was formed. The evaluation criteria are as follows.
[0227] No change in slack: ○
[0228] The amount of relaxation increases slightly: △
[0229] The amount of relaxation increased significantly: ×
[0230] (8) Thermal shrinkage evaluation
[0231] The microporous membrane prepared in (4) above was cut into 10 cm × 10 cm squares along the MD and TD directions, placed in a paper envelope to avoid contact with metal and hot air, and allowed to stand in an oven at 105°C for 1 hour. Then, the microporous membrane was cooled at room temperature, the length L (cm) in the TD direction was measured, and the heat shrinkage was calculated using the following formula.
[0232] TD direction heat shrinkage (%) = (10-L) / 10×100
[0233] The evaluation criteria are as follows.
[0234] Greater than or equal to 0% and less than 4%: ○
[0235] Greater than or equal to 4% and less than 6%: △
[0236] 6% or more:×
[0237] [Production Example] Synthesis of Catalyst
[0238] (Synthesis of solid catalyst component [A-1])
[0239] <(1) Preparation of raw material (a-1)>
[0240] 2,000 mL of 1 mol / L Mg6(C4H9) was added to an 8 L stainless steel autoclave that had been fully purged with nitrogen. 12 To a hexane solution of Al(C2H5)3 (equivalent to 2000 mmol in terms of magnesium and aluminum), 146 mL of a 5.47 mol / L n-butanol hexane solution was added dropwise over 3 hours while stirring at 50°C. After completion, the pipeline was cleaned with 300 mL of hexane.
[0241] Furthermore, stirring was continued at 50° C. for 2 hours. After the reaction was completed, the mixture was cooled to room temperature and the obtained substance was used as raw material (a-1). The raw material (a-1) had a magnesium concentration of 0.715 mol / L.
[0242] <(2) Preparation of raw material (a-2)>
[0243] 2,000 mL of 1 mol / L Mg6(C4H9) was added to an 8 L stainless steel autoclave that had been fully purged with nitrogen. 12A hexane solution of AL(C2H5)3 (equivalent to 2000 mmol of magnesium and aluminum in terms of magnesium and aluminum) was added, and 240 mL of a hexane solution of 8.41 mol / L methyl hydrogen polysiloxane (manufactured by Shin-Etsu Chemical Co., Ltd.) was pumped while stirring at 80°C, and the mixture was stirred for 2 hours at 80°C to react. After the reaction was completed, the mixture was cooled to room temperature and the obtained substance was used as a raw material (a-2). The raw material (a-2) had a total concentration of 0.791 mol / L of magnesium and aluminum.
[0244] <(3) (A-1) Preparation of carrier>
[0245] 1,000 mL of a 1 mol / L hexane solution of hydroxytrichlorosilane was added to an 8L stainless steel autoclave fully purged with nitrogen, and 1340 mL of a hexane solution of the organic magnesium compound of the raw material (a-1) (equivalent to 943 mmoles of magnesium) was added dropwise at 65°C for 3 hours, and the reaction was continued while stirring at 65°C for 1 hour. After the reaction was completed, the supernatant was removed and washed four times with 1,800 mL of hexane to obtain a carrier (A-1). The carrier (A-1) was analyzed, and the magnesium contained in 1 g of solid was 7.5 mmoles.
[0246] <(4) Synthesis of solid catalyst component [A-1]>
[0247] In 1,970 mL of hexane slurry containing 110 g of the above-mentioned (A-1) carrier, 825 mL of a 1 mol / L hexane solution of titanium tetrachloride and 1050 mL of the above-mentioned raw material (a-2) were added simultaneously over 3 hours while stirring at 10°C. After the addition, the reaction was continued at 10°C for 1 hour. After the reaction was completed, the supernatant was removed, and the mixture was washed with hexane 4 times to remove the unreacted raw material components, thereby synthesizing a solid catalyst component [A-1].
[0248] (Synthesis of solid catalyst component [A-2])
[0249] In the synthesis of the above-mentioned solid catalyst component [A-1], the amounts of the hexane solution of titanium tetrachloride and the raw material (a-2) added to the hexane slurry containing the (A-1) carrier were set to 103 mL and 131 mL, respectively. Except for this, the solid catalyst component [A-2] was synthesized in the same manner as the synthesis of the above-mentioned solid catalyst component [A-1].
[0250] (Synthesis of Solid Catalyst Component [B])
[0251] (1) Synthesis of raw material (b-1)
[0252] 2,000 mL of 1 mol / L Mg6(C4H9) was added to an 8 L stainless steel autoclave that had been fully purged with nitrogen. 12 A hexane solution of AL(C2H5)3 (equivalent to 2000 mmol in terms of magnesium and aluminum) was added, and 240 mL of a hexane solution of 8.33 mol / L methyl hydrogen polysiloxane (manufactured by Shin-Etsu Chemical Co., Ltd.) was pumped while stirring at 80°C, and the mixture was stirred for 2 hours at 80°C to react. After the reaction was completed, the mixture was cooled to room temperature and the obtained substance was used as raw material (b-1). The total concentration of magnesium and aluminum in raw material (b-1) was 0.786 mol / L.
[0253] (2) Preparation of solid catalyst component [B]
[0254] 1,600 mL of hexane was added to an 8 L stainless steel autoclave purged with nitrogen. 800 mL of a 1 mol / L hexane solution of titanium tetrachloride and 800 mL of the above raw material (b-1) were added simultaneously over 5 hours while stirring at 10°C. The reaction was continued at 10°C for 1 hour. After the reaction was completed, the supernatant was removed and washed 4 times with hexane to remove the unreacted raw material components, thereby preparing a solid catalyst component [B].
[0255] [Example 1]
[0256] (Method for producing ethylene polymer)
[0257] Hexane, ethylene, hydrogen and catalyst were continuously supplied to a 300L container-type polymerization reactor equipped with a stirring device under the condition of an average residence time of 2 hours. The polymerization pressure was 0.5 MPa. The polymerization temperature was maintained at 83°C by jacket cooling. The catalyst was continuously supplied while being cooled to 4°C.
[0258] As the above-mentioned catalyst, a solid catalyst component [A-1] and triisobutylaluminum as a cocatalyst were used. Triisobutylaluminum was added to the polymerization reactor at a rate of 10 mmol / hour. The solid catalyst component [A-1] was supplied in such a manner that the polymerization rate (production rate) of the ethylene polymer became 10 kg / hour and the slurry concentration in the polymerization reactor became 38% by mass.
[0259] Hydrogen gas was continuously supplied by a pump so that the gas phase concentration became 1.8 mol %.
[0260] The obtained polymer slurry was sent to a centrifugal separator to separate the polymer (polyethylene) and other solvents, thereby obtaining an ethylene polymer. The separated ethylene polymer was dried at 70°C while blowing nitrogen. The ethylene polymer thus obtained was removed using a sieve with a mesh size of 425 μm to obtain polyethylene powder. The catalytic activity was 13970 g-PE / g-catalyst (13970 g of polyethylene powder per 1 g of catalyst).
[0261] The properties of the obtained polyethylene powder were measured by the above-mentioned methods. The measurement results are shown in Table 1 below.
[0262] [Example 2]
[0263] In the polymerization step, the hydrogen concentration of the gas phase was set to 9.1 mol % and the catalyst was introduced in a manner such that the slurry concentration was 20%. Polyethylene powder was obtained by the same operation as in [Example 1] above. The catalyst activity was 18372 g-PE / g-catalyst. The properties of the obtained polyethylene powder are shown in Table 1 below.
[0264] [Example 3]
[0265] In the polymerization step, the polymerization temperature was set to 70°C, the hydrogen concentration in the gas phase was set to 9.4 mol%, and 1-butene as a copolymer component was continuously introduced so that the gas phase concentration became 0.15 mol%. Polyethylene powder was obtained by the same operation as in the above [Example 1]. The catalyst activity was 11989 g-PE / g-catalyst. The properties of the obtained polyethylene powder are shown in the following Table 1.
[0266] [Example 4]
[0267] In the polymerization step, a polyethylene powder was obtained by the same operation as in the above-mentioned [Example 1] except that [A-2] was used as a solid catalyst component and the catalyst was introduced in a manner such that the slurry concentration was 35% by mass. The catalyst activity was 19598 g-PE / g-catalyst. The properties of the obtained polyethylene powder are shown in the following Table 1.
[0268] [Example 5]
[0269] Polyethylene powder was obtained by the same operation as in Example 1 except that the hydrogen concentration in the gas phase was set to 0.4 mol % in the polymerization step. The catalyst activity was 35184 g-PE / g-catalyst. The properties of the obtained polyethylene powder are shown in Table 1 below.
[0270] [Example 6]
[0271] In the polymerization step, the hydrogen concentration of the gas phase was set to 15.1 mol%, the catalyst was introduced so as to have a slurry concentration of 40 mass%, and the catalyst was intermittently supplied while being kept at 60° C. The polyethylene powder was obtained by the same operation as in the above-mentioned [Example 1]. The catalyst activity was 10201 g-PE / g-catalyst. The properties of the obtained polyethylene powder are shown in the following Table 1.
[0272] [Example 7]
[0273] In the polymerization step, the polymerization temperature was set to 70° C., the hydrogen concentration in the gas phase was set to 0.03 mol %, and the catalyst was introduced so that the slurry concentration was 36 mass %, and polyethylene powder was obtained by the same operation as in the above [Example 1]. The catalyst activity was 45839 g-PE / g-catalyst. The properties of the obtained polyethylene powder are shown in the following Table 1.
[0274] [Comparative Example 1]
[0275] In the polymerization step, the hydrogen concentration in the gas phase was set to 7.8 mol%, 1-butene as a copolymer component was continuously introduced in such a manner that the gas phase concentration was 0.15 mol%, [B] was used as a solid catalyst component, the temperature when the catalyst was introduced was set to 60°C, and the amount of catalyst introduced was set in such a manner that the slurry concentration was 31 mass%, and polyethylene powder was obtained by the same operation as in [Example 1] above. The catalyst activity was 20411 g-PE / g-catalyst. The properties of the obtained polyethylene powder are shown in Table 1 below.
[0276] [Comparative Example 2]
[0277] In the polymerization step, the polymerization temperature was set to 70°C, the hydrogen concentration in the gas phase was set to 0.01 mol%, the catalyst was introduced in a manner such that the slurry concentration became 25 mass%, and the temperature when the catalyst was introduced was set to 60°C. Polyethylene powder was obtained by the same operation as in [Example 1] above. The catalyst activity was 45022 g-PE / g-catalyst. The intrinsic viscosity (IV) of the polyethylene powder was high, and it was not possible to properly form a film and could not be evaluated. The properties of the obtained polyethylene powder are shown in Table 1 below.
[0278] [Comparative Example 3]
[0279] In the polymerization step, the polymerization temperature was set to 70°C, the hydrogen concentration in the gas phase was set to 18.5 mol%, 1-butene as a copolymer component was continuously introduced in a manner that the gas phase concentration was 0.8 mol%, and [A-2] was used as a solid catalyst component, and the catalyst was introduced in a manner that the slurry concentration was 25 mass%. Polyethylene powder was obtained by the same operation as in [Example 1] above. The catalyst activity was 8423 g-PE / g-catalyst. The properties of the obtained polyethylene powder are shown in Table 1 below.
[0280]
[0281] In the examples, polyethylene powders were obtained which had few film defects, small extruder pressure increase, small heat shrinkage, and little relaxation over time.
[0282] This application is based on Japanese Patent Application (Japanese Patent Application No. 2020-094628) filed with the Japan Patent Office on May 29, 2020, the contents of which are incorporated herein by reference.
[0283] Industrial Applicability
[0284] The polyethylene powder of the present invention has industrial applicability as a material for various molded bodies, microporous films, battery separators, and fibers.
Claims
1. A polyethylene powder, wherein: The polyethylene powder satisfies the following requirements 1 and 2: Requirement 1: The viscosity change rate of the gel obtained under the following gel preparation conditions under the following viscosity change rate measurement conditions is -0.8 Pas / °C or more and 0.0 Pas / °C or less, Gel preparation conditions: Using a torque rheometer of model 4C150 and mixer model R-60 manufactured by Toyo Seiki Co., Ltd., 28 g of liquid paraffin having an average molecular weight of 450 g / mol or more and less than 550 g / mol, 12 g of polyethylene powder, and 0.4 g of tetrakis[methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate)]methane were kneaded for 10 minutes at a set temperature of 200° C. and a rotation speed of 50 rpm to obtain a gel. Viscosity change rate measurement conditions: According to the flow characteristics test using a capillary die specified in JIS K7199, a capillary die with a capillary diameter of 0.77 mm, a length of 50.80 mm, an inflow angle of 90°, a piston speed of 10 mm / min, a shear rate of 266 s -1 The viscosity at set temperatures of 200°C and 230°C is measured, the unit of which is Pas, and the viscosity change rate is calculated according to the following formula (1), the unit of which is Pas / °C, In formula (1), η(A,B) represents the shear rate As -1 , viscosity measured at temperature B℃; Requirement 2: The intrinsic viscosity (IV) is 1.5 dL / g or more and less than 18.0 dL / g.
2. The polyethylene powder according to claim 1, wherein At shear speed 266s -1 , the viscosity η(266,200) of the gel at a set temperature of 200° C. is greater than or equal to 100 Pas and less than or equal to 300 Pas.
3. The polyethylene powder according to claim 1 or 2, wherein: The gel obtained by the gel preparation conditions, according to the viscosity change rate measurement conditions, at a shear rate of 11s -1 , the viscosity of the gel measured at a set temperature of 200°C and at a shear rate of 533s -1 , log(η(11,200) / η(533,200)) of the viscosity of the gel measured at a set temperature of 200° C. is 1.00 or more and 1.80 or less.
4. The polyethylene powder according to claim 1 or 2, wherein The polyethylene powder is an ethylene homopolymer.
5. The polyethylene powder according to claim 1 or 2, wherein: The isothermal crystallization time of the polyethylene powder at 125° C. obtained under the following isothermal crystallization time measurement conditions is less than 7.0 minutes, Isothermal crystallization time determination conditions: Step A1: maintain at 50°C for 1 minute, then increase the temperature to 180°C at a rate of 10°C / min; Step A2: maintaining at 180°C for 5 minutes, and then cooling to 125°C at a cooling rate of 80°C / min; Step A3: Maintain at 125°C, The time when the temperature reaches 125° C. is defined as the starting point, i.e., 0 minute, and the time when the exothermic peak due to crystallization is obtained is defined as the isothermal crystallization time.
6. The polyethylene powder according to claim 1 or 2, wherein: The ethylene polymer constituting the polyethylene powder is an ethylene copolymer.
7. The polyethylene powder according to claim 6, wherein The ethylene copolymer has branches.
8. The polyethylene powder according to claim 6, wherein The ethylene copolymer comprises a copolymer component, and the copolymer component is an α-olefin and / or a vinyl compound.
9. The polyethylene powder according to claim 8, wherein The α-olefin is an α-olefin having 3 to 20 carbon atoms.
10. The polyethylene powder according to claim 8, wherein The α-olefin is one or more of propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene and 1-tetradecene.
11. The polyethylene powder according to claim 8, wherein The vinyl compound is one or more of vinylcyclohexane, styrene and derivatives thereof.
12. The polyethylene powder according to claim 8, wherein The copolymerization component further comprises a non-conjugated polyene.
13. The polyethylene powder according to claim 12, wherein The non-conjugated polyene is one or more of 1,5-hexadiene and 1,7-octadiene.
14. The polyethylene powder according to claim 1 or 2, wherein: The polyethylene powder has an average particle size of 5 μm or more and 500 μm or less.
15. The polyethylene powder according to claim 1 or 2, wherein: The polyethylene powder has an average particle size of 10 μm or more and 300 μm or less.
16. The polyethylene powder according to claim 1 or 2, wherein: The polyethylene powder has an average particle size of 10 μm or more and 150 μm or less.
17. The polyethylene powder according to claim 1 or 2, wherein: The density of the polyethylene powder is 910 kg / m 3 Above and 980kg / m 3 the following.
18. The polyethylene powder according to claim 1 or 2, wherein: The density of the polyethylene powder is 915 kg / m 3 Above and 970kg / m 3 the following.
19. The polyethylene powder according to claim 1 or 2, wherein: The density of the polyethylene powder is 920 kg / m 3 Above and 965kg / m 3 the following.
20. The polyethylene powder according to claim 1 or 2, wherein: The viscosity change rate is greater than or equal to -0.5 Pas / °C and less than or equal to 0.0 Pas / °C.
21. The polyethylene powder according to claim 1 or 2, wherein: The viscosity change rate is greater than or equal to -0.2 Pas / °C and less than or equal to 0.0 Pas / °C.
22. The polyethylene powder according to claim 1 or 2, wherein: In the method for producing polyethylene powder, polymerization is performed using a catalyst having an active site density in a saturated state.
23. The polyethylene powder according to claim 1 or 2, wherein: In the method for producing polyethylene powder, the polymerization temperature is 80° C. or higher.
24. The polyethylene powder according to claim 1 or 2, wherein: In the method for producing the polyethylene powder, the slurry concentration in the polymerization reactor, that is, the solid content ratio in the liquid phase is 35% by mass or more.
25. The polyethylene powder according to claim 1 or 2, wherein: In the method for producing polyethylene powder, the catalyst activity during polymerization is 30,000 g-PE / g-catalyst or less.
26. The polyethylene powder according to claim 1 or 2, wherein: In the method for producing polyethylene powder, the catalyst is continuously supplied at a temperature that is 50° C. or more lower than the polymerization temperature.
27. The polyethylene powder according to claim 1 or 2, wherein: The intrinsic viscosity of the polyethylene powder is greater than or equal to 2.0 dL / g and less than 15.0 dL / g.
28. The polyethylene powder according to claim 1 or 2, wherein: The polyethylene powder has an intrinsic viscosity of greater than or equal to 2.4 dL / g and less than 7.1 dL / g.
29. The polyethylene powder according to claim 1 or 2, wherein: At shear speed 266s -1 , the viscosity η(266,200) of the gel at a set temperature of 200° C. is greater than or equal to 120 Pas and less than or equal to 250 Pas.
30. The polyethylene powder according to claim 1 or 2, wherein: At shear speed 266s -1 , the viscosity η(266,200) of the gel at a set temperature of 200° C. is greater than or equal to 140 Pas and less than or equal to 230 Pas.
31. The polyethylene powder according to claim 1 or 2, wherein: The gel obtained by the gel preparation conditions, according to the viscosity change rate measurement conditions, at a shear rate of 11s -1 , the viscosity of the gel measured at a set temperature of 200°C and at a shear rate of 533s -1 , log(η(11,200) / η(533,200)) of the viscosity of the gel measured at a set temperature of 200° C. is greater than or equal to 1.10 and less than or equal to 1.
60.
32. The polyethylene powder according to claim 1 or 2, wherein: The gel obtained by the gel preparation conditions, according to the viscosity change rate measurement conditions, at a shear rate of 11s -1 , the viscosity of the gel measured at a set temperature of 200°C and at a shear rate of 533s -1 , log(η(11,200) / η(533,200)) of the viscosity of the gel measured at a set temperature of 200° C. is 1.20 or more and 1.50 or less.
33. The polyethylene powder according to claim 1 or 2, wherein: The isothermal crystallization time of the polyethylene powder at 125° C. is less than 4.0 minutes.
34. The polyethylene powder according to claim 1 or 2, wherein: The isothermal crystallization time of the polyethylene powder at 125° C. is less than 3.0 minutes.
35. The polyethylene powder according to claim 1 or 2, wherein: The isothermal crystallization time of the polyethylene powder at 125° C. is 1.0 minute or longer.
36. The polyethylene powder according to claim 1 or 2, wherein: The polyethylene powder is obtained by copolymerizing or polymerizing ethylene or a monomer including ethylene using any one of a slurry polymerization method, a gas phase polymerization method, and a solution polymerization method.
37. The polyethylene powder according to claim 1 or 2, wherein: The polyethylene powder is obtained by copolymerizing or polymerizing ethylene or a monomer including ethylene using a slurry polymerization method.
38. The polyethylene powder of claim 37, wherein In the slurry polymerization method, an inert hydrocarbon medium or olefin itself is used as the medium.
39. The polyethylene powder of claim 38, wherein The inert hydrocarbon medium is selected from aliphatic hydrocarbons such as propane, butane, isobutane, pentane, isopentane, hexane, heptane, octane, decane, dodecane, kerosene, etc.; alicyclic hydrocarbons such as cyclopentane, cyclohexane, methylcyclopentane, etc.; aromatic hydrocarbons such as benzene, toluene, xylene, etc.; halogenated hydrocarbons such as ethyl chloride, chlorobenzene, dichloromethane, etc.; and mixtures thereof.
40. The polyethylene powder according to claim 1 or 2, wherein: In the method for producing the polyethylene powder, the polymerization temperature is 80° C. or higher and 100° C. or lower.
41. The polyethylene powder according to claim 1 or 2, wherein: In the method for producing the polyethylene powder, the polymerization pressure is 0.10 MPa to 2.0 MPa.
42. The polyethylene powder according to claim 1 or 2, wherein: In the method for producing the polyethylene powder, the polymerization pressure is 0.10 MPa to 1.5 MPa.
43. The polyethylene powder according to claim 1 or 2, wherein: In the method for producing polyethylene powder, the polymerization pressure is 0.10 MPa to 1.0 MPa.
44. The polyethylene powder according to claim 1 or 2, wherein: In the method for producing the polyethylene powder, the slurry concentration in the polymerization reactor, that is, the solid content ratio in the liquid phase is 35 mass % or more and 45 mass % or less.
45. The polyethylene powder according to claim 1 or 2, wherein: In the method for producing polyethylene powder, the activity of the catalyst during polymerization is 8,000 g-PE / g-catalyst or more and 30,000 g-PE / g-catalyst or less.
46. The polyethylene powder according to claim 1 or 2, wherein: In the method for producing the polyethylene powder, the polymerization reaction is carried out by any one of a batch method, a semi-continuous method and a continuous method.
47. The polyethylene powder according to claim 1 or 2, wherein: In the method for producing polyethylene powder, the polymerization reaction is carried out by continuous polymerization.
48. The polyethylene powder according to claim 1 or 2, wherein: In the method for producing polyethylene powder, the catalyst component used is a Ziegler-Natta catalyst, a metallocene catalyst or a Phillips catalyst.
49. The polyethylene powder according to claim 1 or 2, wherein: In the method for producing polyethylene powder, the catalyst component used includes a co-catalyst.
50. The polyethylene powder of claim 49, wherein The co-catalyst is triisobutylaluminum or Tebbe reagent.
51. The polyethylene powder according to claim 1 or 2, wherein: In the method for producing polyethylene powder, the catalyst is cooled so that the temperature difference from the polymerization temperature is 50° C. or more and 70° C. or less, and the catalyst is continuously introduced into the polymerizer in the cooled state.
52. The polyethylene powder according to claim 1 or 2, wherein: In the method for producing polyethylene powder, the catalyst used has an average particle size of 0.1 μm or more and 20 μm or less.
53. The polyethylene powder according to claim 1 or 2, wherein: In the method for producing polyethylene powder, the catalyst used has an average particle size of 0.2 μm or more and 16 μm or less.
54. The polyethylene powder according to claim 1 or 2, wherein: In the method for producing polyethylene powder, the catalyst used has an average particle size of 0.5 μm or more and 12 μm or less.
55. The polyethylene powder according to claim 1 or 2, wherein: In the method for producing the polyethylene powder, the catalyst is deactivated after the polyethylene powder is separated from the solvent.
56. The polyethylene powder according to claim 1 or 2, wherein: In the method for producing the polyethylene powder, 0 mol % or more and 30 mol % or less of hydrogen is added to the polymerization system.
57. The polyethylene powder according to claim 1 or 2, wherein: In the method for producing the polyethylene powder, 0 mol % or more and 25 mol % or less of hydrogen is added to the polymerization system.
58. The polyethylene powder according to claim 1 or 2, wherein: In the method for producing the polyethylene powder, 0 mol % or more and 20 mol % or less of hydrogen is added to the polymerization system.
59. The polyethylene powder according to claim 1 or 2, wherein: In the method for producing the polyethylene powder, a drying step is performed after the polyethylene powder and the solvent are separated.
60. The polyethylene powder of claim 59, wherein The drying temperature in the drying step is 50° C. or higher and 150° C. or lower.
61. The polyethylene powder of claim 59, wherein: The drying temperature in the drying step is 50° C. or higher and 140° C. or lower.
62. The polyethylene powder of claim 59, wherein The drying temperature in the drying step is 50° C. or higher and 130° C. or lower.
63. The polyethylene powder according to claim 1 or 2, wherein: The polyethylene powder further comprises additives.
64. The polyethylene powder of claim 63, wherein The additive is one or more of a neutralizer, an antioxidant and a light stabilizer.
65. The polyethylene powder of claim 63, wherein The content of the additive is 5,000 ppm or less relative to the total amount of polyethylene.
66. The polyethylene powder of claim 64, wherein The neutralizing agent is an alkaline earth metal stearate.
67. The polyethylene powder of claim 64, wherein The antioxidant is selected from butylated hydroxytoluene, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate.
68. The polyethylene powder of claim 64, wherein The light-resistant stabilizer is selected from 2-(5-methyl-2-hydroxyphenyl)benzotriazole, 2-(3-tert-butyl-5-methyl-2-hydroxyphenyl)-5-chlorobenzotriazole; bis(2,2,6,6-tetramethyl-4-piperidinyl)sebacate, poly[{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl}{(2,2,6,6-tetramethyl-4-piperidinyl)imino}hexamethylene{(2,2,6,6-tetramethyl-4-piperidinyl)imino}].
69. A molded body, wherein The molded body is a molded body of the polyethylene powder according to any one of claims 1 to 68.
70. The molded article according to claim 69, wherein The molded article is evaluated as ○ or △ in the following film defect evaluation, Film defect evaluation The number of defects having a diameter of 0.2 mm or more present in an area of 25 cm×25 cm of the molded body is visually determined, The evaluation criteria are as follows: Greater than or equal to 0 / 625cm 2 And less than 4 / 625cm 2 :○ More than or equal to 4 / 625cm 2 And less than 7 / 625cm 2 :△ 7pcs / 625cm 2 Above: ×.
71. The molded article according to claim 69 or 70, wherein The molded product was evaluated as ○ or △ in the following extruder pressure increase evaluation, Extruder boost evaluation In the production of the molded body, the pressure was measured using a resin pressure gauge installed upstream of the circuit breaker panel, and the difference between the average value of the resin pressure 10 minutes after the start of extrusion and the average value of the resin pressure 10 minutes before the end of extrusion was evaluated as the pressure increase amount. The evaluation criteria are as follows: Greater than or equal to 0MPa and less than 0.5MPa: ○ Greater than or equal to 0.5MPa and less than 1.0MPa: △ 1.0MPa and above: ×.
72. The molded article according to claim 69 or 70, wherein The molded body is evaluated as ○ or △ in the following relaxation evaluation, Relaxation Evaluation The molded body was pulled out for 3 m, and the four corners were held and the body was horizontally stretched in the air, and local slack that could be confirmed by visual observation was evaluated. The local slack was evaluated to what extent it deteriorated after being left to stand at room temperature for one week while being held on a roll compared to that immediately after film formation. The evaluation criteria are as follows: No change in slack: ○ Slightly increased relaxation: △ The amount of relaxation increased significantly: ×.
73. The molded article according to claim 69 or 70, wherein The molded article is evaluated as ○ or △ in the following heat shrinkage evaluation, Thermal shrinkage evaluation The molded body was cut into 10 cm × 10 cm squares along the MD and TD directions, and placed in a paper envelope to avoid contact with metal and hot air, and allowed to stand in an oven at 105°C for 1 hour. Then, the microporous membrane was cooled at room temperature, and the length L in the TD direction was measured. The unit of the length L was cm, and the heat shrinkage was calculated using the following formula: TD direction heat shrinkage (%) = (10-L) / 10×100 The evaluation criteria are as follows: Greater than or equal to 0% and less than 4%: ○ Greater than or equal to 4% and less than 6%: △ 6% or more: ×.
74. The molded article according to claim 69 or 70, wherein The molded body is a battery separator.
75. The molded article according to claim 69 or 70, wherein The molded body is a separator for a lithium ion secondary battery.
Citation Information
Patent Citations
PROCESS FOR THE PRODUCTION OF POLYOLEFINS AND THEIR COPOLYMERISATS
DE3127133A1
JP1973068853A
Emergency illuminator
JP1982067202A
Separator for battery and manufacture thereof
JP1990021559A
Catalyst for olefin polymerization and method for polymerizing olefin
JP2006273977A